Microarc-oxidized titanium surfaces functionalized with microRNA-21-loaded chitosan/hyaluronic acid nanoparticles promote the osteogenic differentiation of human bone marrow mesenchymal stem cells - Wang Z (Dove Medical Press, 2015)
Zhongshan Wang,1,* Guangsheng Wu,2,3,* Zhihong Feng,1 Shizhu Bai,1 Yan Dong,1 Guofeng Wu,1 Yimin Zhao1 1State Key Laboratory of Military Stomatology, Department of Prosthetic Dentistry, 2State Key Laboratory of Military Stomatology, Department of Periodontology, School of Stomatology, The Fourth Military Medical University, Xi’an, People’s Republic of China; 3Qingdao First Sanatorium, Jinan Military Region, Qingdao, Shandong Province, People’s Republic of China *These authors contributed equally to this work Abstract: Dental implants have been widely used for the replacement of missing teeth in the clinic, but further improvements are needed to meet the clinical demands for faster and tighter osseointegration. In this study, we fabricated safe and biocompatible chitosan (CS)/hyaluronic acid (HA) nanoparticles to deliver microRNA-21 (miR-21) and thereby accelerate osteogenesis in human bone marrow mesenchymal stem cells (hBMMSCs). The CS/HA/miR-21 nanoparticles were cross-linked with 0.2% gel solution onto microarc oxidation (MAO)-treated titanium (Ti) surfaces to fabricate the miR-21-functionalized MAO Ti surface, resulting in the development of a novel coating for reverse transfection. To characterize the CS/HA/miR-21 nanoparticles, their particle size, zeta potential, surface morphology, and gel retardation ability were sequentially investigated. Their biological effects, such as cell viability, cytotoxicity, and expression of osteogenic genes by hBMMSCs on the miR-21-functionalized MAO Ti surfaces, were evaluated. Finally, we explored appropriate CS/HA/miR-21 nanoparticles with a CS/HA ratio of 4:1 and N/P ratio 20:1 for transfection, which presented good spherical morphology, an average diameter of 160.4±10.75 nm, and a positive zeta potential. The miR-21-functionalized MAO Ti surfaces demonstrated cell viability, cytotoxicity, and cell spreading comparable to those exhibited by naked MAO Ti surfaces and led to significantly higher expression of osteogenic genes. This novel miR-21-functionalized Ti implant may be used in the clinic to allow more effective and robust osseointegration. Keywords: titanium implants, microarc oxidation, human bone marrow MSCs, microRNA, nanoparticles, osteogenic differentiation